Pencegahan Stanting Lembang Tondon Langi Kecamatan Tondon Kabupaten Toraja Utara - Permata Sari; Heppyanti Ponno; Gabryella Ivanka Rerungan; Helba Rundupadang; Intan Intan (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
Community Service (PKM) which is located in Lembang Tondon Langi', Tondon District, North Toraja Regency is one of the places where we served for approximately one and a half months. In the work program that we are implementing, the focus is more on preventing stunting that occurs in Lembang Tondon Langi'. Where this work program is one of the themes that has been determined by the campus, namely "Stunting Prevention". This work program aims to help stunting cadres and the community, especially mothers, in providing adequate nutrition for their children. The specific target of this program is to improve nutritional intake which is still not good in Lembang Tondon Langi'. This program also aims to reduce the potential for stunting in Lembang Tondon Langi', Tondon District, North Toraja Regency. However, there is a problem encountered in Lembang Tondon Langi', Tondon District, North Toraja Regency, namely that there is no awareness among some communities about the importance of adequate nutritional intake for their children. The initial step taken in this activity is to design and organize activities related to stunting as well as carry out outreach to school children and the community.